A Novel Method to Determine the Cause of Left Internal Mammary Artery Instant Non-Patency Based on Transit Time Flow Measurement - Mao, Boyan; Feng, Yue; Duan, Mengyao; Dong, Yihang; Li, Gaoyang; Li, Bao; Liu, Jincheng; Guo, Yuting; Wei, Minghui; Zhao, Zhou; Liu, Youjun (Frontiers in Physiology, 2022)
Objective: After coronary artery bypass grafting (CABG) surgery, the main causes of poor instant patency of left internal mammary arteries (LIMA) are competitive flow and anastomotic stenosis, but how to determine the cause of LIMA non-patency without interfering with the target coronary artery is still a difficult problem to be solved urgently. Methods: In this study, the 0D-3D coupled multi-scaled CABG model of anastomotic stenosis and competitive flow was constructed. After calculation, the flow waveform of LIMA was extracted, and the waveform shape, common clinical parameters (average flow, PI, DF) and graft flow FFT ratio results (F0/H1 and F0/H2) were analyzed. Results: For LIMA, these three common clinical parameters did not differ significantly between the anastomotic stenosis group and the competitive flow group. However, the waveform shape and FFT ratio (especially F0/H2) of the competitive flow group were significantly different from that of the anastomotic stenosis group. When the cause was competitive flow, there was systolic backflow and F0/H2 was too high (> 14.89). When the cause was anastomotic stenosis, the waveform maintained a bimodal state and F0/H2 was in a normal state (about 1.17). Conclusion: When poor instant patency of LIMA is found after CABG, the causes can be determined by graft flow waveform shape and F0/H2.